(3eWdY GdHOhQ heLeY GdHMhQs - (3CMeO Hf UGdM Hf CHj GdQLGd Gdjefj, Uaj GdOjf ,GHf nCHj GdpqQnLGd,J (B1092 (3g` s ((3GdQhVI HCWQGa UfYGA s)
(3ChdgG (B:s
(3ef HGH ef GSeg GdMSf , JQLeI (B: (3GdMSf Hf EHQGgje Hf YHO Gddg Hf GdMSf cGf hLgkG eJbOekG ai GdaVd s
(3BNQgG (B:s
(3hjcf HGdfGUQ hOaf HbHJg GdeYQhaI hcGfJ haGJg jhe GdNejS ced GdLRA GdKGfi ef eWdY hjdi gPG GdLRA GdLRA GdKGdK hChdg MQa GdWGA s
(3HgG fXGe GdJYbjHIs
(3HBNQgG JQLeI ddeDda ai (B25 (3dhMIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B137 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B253s
Keywords: (3GdJGQjNs